Impact of Cladding Tubes in Chalcogenide Negative Curvature Fibers - Chengli Wei; Curtis R. Menyuk; Jonathan Hu (IEEE Photonics Journal, 2016)
We computationally study the leakage loss and bandwidth in chalcogenide negative curvature fibers. The leakage loss is decreased by a factor of 19, and the operating bandwidth is almost doubled when the optimal gap between cladding tubes is used in negative curvature fibers with six tubes. There is a wide range of the gaps between 5 and 40 $μ\text{m}$ , which gives a leakage loss lower than 0.04 dB/m and a wide transmission bandwidth of 1.1 $μ\text{m}$ . The optimal gap in a fiber with six cladding tubes is three times as large as the optimal gap in fibers with eight or ten cladding tubes. A larger gap is needed in a fiber with six cladding tubes to remove the weak coupling between the central core mode and the tube modes. This design of the chalcogenide negative curvature fibers using a wide range of gaps will lead to successful fiber devices with a low loss and a wide bandwidth for mid-IR transmission.